INTER-RELIGIOUS DIALOGUE AS A MEDIUM OF CONTEMPORARY ISLAMIC DA’WAH - Jaffary Awang; Umar Faruk; hasnan bin kasan (UIN Syarif Hidayatullah Jakarta, 2019)
Abstract. Interfaith dialogue is a form of discussion and information exchange between the devotees of different religions, while da’wah is a form of preaching to Islam. In the context of opportunity, Muslims should accept the challenge of participation in interfaith dialogue. So thus preparation and knowledge about da’wah and interreligious dialogue has become a necessity before involving in interfaith dialogue. Based on the nature of inter-religious dialogue that emphasizes on openness, willingness to listen to different views and based on knowledge, then this method should be taken seriously by the Muslim in the context of contemperory da’wah to propagate Islam to the masses. Finally this paper concluded interfaith dialogue in Malaysia has a great potential and in the growing interest among the Muslim community in particular. Abstrak. Dialog antaragama adalah bentuk diskusi dan pertukaran informasi antara para pemeluk agama yang berbeda, sementara dakwah adalah bentuk dakwah kepada Islam. Dalam konteks kesempatan, umat Islam harus menerima tantangan partisipasi dalam dialog antaragama. Jadi persiapan dan pengetahuan dakwah dan dialog antaragama telah menjadi kebutuhan sebelum terlibat dalam dialog antaragama. Berdasarkan pada sifat dialog antar agama yang menekankan pada keterbukaan, kesediaan untuk mendengarkan pandangan yang berbeda dan berdasarkan pada pengetahuan, maka metode ini harus ditanggapi dengan serius oleh Muslim dalam konteks kontekstualisasi dakwah untuk menyebarkan Islam kepada massa. Akhirnya makalah ini menyimpulkan dialog antaragama di Malaysia memiliki potensi besar dan dalam minat yang tumbuh di kalangan komunitas Muslim pada khususnya.